2017
DOI: 10.1136/vetreco-2016-000199
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of InlA truncation in Listeria monocytogenes isolates from farm animals and human cases in the province of Quebec

Abstract: The introduction of Listeria monocytogenes into the food production chain is a concern, with numerous grouped cases of listeriosis associated with milk-derived or pork-derived products have been documented. Management of this zoonotic pathogen considers all strains as an equal risk. Recently, a new perspective for characterisation of strain virulence was introduced with the discovery of the unaltered sequence of InlA as a determinant of strain virulence; this has also been reported as an infrequent finding amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…Meanwhile, the other nine isolates carrying the same PCMS mutations were from chicken, pork and beef, respectively. InlA mutation isolates had a widespread distribution and we also noticed L. monocytogenes isolates with PMSCs might still cause listeriosis (human isolate SHL006 carrying a PMSC mutation), which have been reported in previous studies [17, 21, 31, 58]. It is also important to note that L. monocytogenes infection is related to additional factors such as dietary intake, and health condition (pregnant women and the elderly) [24].…”
Section: Discussionsupporting
confidence: 69%
“…Meanwhile, the other nine isolates carrying the same PCMS mutations were from chicken, pork and beef, respectively. InlA mutation isolates had a widespread distribution and we also noticed L. monocytogenes isolates with PMSCs might still cause listeriosis (human isolate SHL006 carrying a PMSC mutation), which have been reported in previous studies [17, 21, 31, 58]. It is also important to note that L. monocytogenes infection is related to additional factors such as dietary intake, and health condition (pregnant women and the elderly) [24].…”
Section: Discussionsupporting
confidence: 69%
“…Notably, the clinical isolates characterised in the present study belong to serogroup IVb, which includes serotypes 4b, 4d, and 4e. This group has been found in several clinical cases from both humans and different farm animal species, such as cattle, sheep, poultry and swine, in different countries ( 46 48 ). Serogroup IVb has also been found to be the predominant group among cases of listeriosis in small ruminants in Greece ( 49 ), accounting for 68% of all clinical isolates from encephalitis cases and 57% of the isolates from milk samples.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, not all L monocytogenes strains are equally virulent; some strains are highly virulent and are more often associated with epidemics, while others are less virulent and are infrequently related to epidemics. [1][2][3] Previous studies have shown that lineage I (or ST 4b) occurs more frequently among clinical isolates than lineage II (or ST 1/2b, ST 1/2a and ST 1/2 c), relative to the frequency of these categories in food. 4 Besides intrinsic L monocytogenes virulence, other extrinsic factors play an equally important role in listeriosis outbreaks, such as individual susceptibility, food category, good hygiene practices and good manufacturing practices, and persistence into the environment or biofilm formation, among others.…”
Section: Discussionmentioning
confidence: 99%
“…Although all L monocytogenes strains are currently treated equally for regulatory purposes, some strains are highly virulent and are more often associated with epidemics, while others are less virulent and are infrequently related to epidemics. [1][2][3] Particularly, in human listeriosis outbreaks, isolates belonging to serotype (ST) 4b are over-represented, with a lower number of cases associated with isolates from ST 1/2a, which is usually associated with food and food-related L monocytogenes isolates. 4 5 In 2018, 28 countries reported 2549 conirmed cases of listeriosis in the EU/EEA, with more than 229 associated deaths.…”
Section: Introductionmentioning
confidence: 99%